Introduction: guest editorial for special issue ‘gender and im(mobilities) - Pavlovskaya, Marianna; Gerrard, Siri; Aure, Marit (Gender, Place & Culture, 2019)
This is an Accepted Manuscript of an article published by Taylor & Francis in Gender, Place & Culture on 13. Feb. 2019, available online: http://www.tandfonline.com/https://doi.org/10.1080/0966369X.2018.1499618. The research articles in this themed section examine gendered constellations of (im)mobilities with respect to work, class, livelihoods, and place. The issue includes selected articles presented at the interdisciplinary conference ‘Gender and (Im)mobilities in the Context of Work’ that took place in Tromsø, Norway June 15-17, 2016. To address different aspects of interlinking mobility, immobility, gender, and economy, the authors use feminist theoretical frameworks developed in various academic disciplines together with a range of methods, ranging from ethnography to quantitative analysis and innovative combinations of both. The first set of articles that examine the gendering of spaces of everyday mobile work also highlight the relationship between place and gendered narratives of the economy, mobility and fixity and show that mobility is integral to construction of and thinking about place. In the second set of articles, the focus shifts to the households of mobile workers and/or the mobile workers themselves. Despite being separated by large distances, home and place of work remain intimately connected and fused with each other in many ways. Mobile work changes gender relations within the households while mobile workplaces are constantly affected by workers caring for family left behind and the need for care work for the mobile workforce that commonly happens in the households.